Dose-reduced combination of mitoxantrone, etoposide, and cytarabine (miniMEC) for relapsed and refractory acute leukemia. Issue 11 (1st November 2016) - Yamamoto, Chihiro; Ito, Shoko; Mashima, Kiyomi; Umino, Kento; Minakata, Daisuke; Yamasaki, Ryoko; Kawasaki, Yasufumi; Sugimoto, Miyuki; Nakano, Hirofumi; Ashizawa, Masahiro; Okazuka, Kiyoshi; Hatano, Kaoru; et al.
Abstract: The combination of mitoxantrone (MIT), etoposide (ETP), and cytarabine (Ara-C) (MEC) is a frequently used salvage therapy for acute leukemia, but has been associated with severe myelosuppression. Therefore, we investigated the miniMEC regimen with reduced doses of AraC and MIT. Thirteen ALL and 44 AML patients, all relapsed or refractory, received miniMEC, which consisted of MIT at 8 mg/m 2 for 3 d, ETP at 100 mg/m 2 for 5 d, and Ara-C at 100 mg/m 2 infused over 24 h for 7 d. CR + CRi was achieved in eight ALL patients (61.5%) and 16 AML patients (36.4%). Median duration of neutropenia was 30 d (range, 1–50). Thirty-one patients (54.4%) subsequently received allogeneic stem cell transplantation (SCT), and overall survival was significantly improved in this group (median OS 161 versus 481 d, p = 0.006). We concluded that miniMEC is a safe and effective bridging therapy to SCT.